Doxycycline: An Old Drug with A New Role in Idiopathic Pulmonary Fibrosis - GYANSHANKAR P. MISHRA,; JASMIN D. MULANI, (International Journal of Pharma and Bio Sciences, 2010)
Given the lack of knowledge of the etiology, pathogenesis and natural history of IPF, it is perhaps not surprising that that there is a lack of high quality evidence for the 'standard' treatments currently in use. In such a scenario the ideal therapy for IPF is still awaited. The present article reviews the potential role of doxycycline as a novel therapeutic option in the treatment of IPF substantiated by results of relevant studies on doxycycline. The Matrix metalloproteinases (MMP) inhibitor property of doxycycline may help it gain its role in IPF in years to come.